2013
DOI: 10.1007/s10899-013-9373-x
|View full text |Cite
|
Sign up to set email alerts
|

Professional Help-Seeking for Gambling Problems: Awareness, Barriers and Motivators for Treatment

Abstract: Despite the negative consequences associated with gambling, few problem gamblers seek professional help. This study aimed to examine awareness of professional sources of help and help-seeking behaviour amongst regular and problem gamblers. Australian gamblers (N = 730) were recruited from the general population, multicultural gambling venues, and gambling helplines and treatment services. Surveys measured awareness of professional help services, help-seeking behaviour and motivators and barriers to seeking hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
167
3
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(188 citation statements)
references
References 32 publications
7
167
3
11
Order By: Relevance
“…Deep shame was a near universal emotion amongst participants with self-stigmatizing beliefs, prompting secrecy as the main coping mechanism (Link et al, 2004) to preserve a (problem-free) social and subjective identity (Goffman, 1963). The findings confirmed that perceived and self-stigma are major barriers to seeking help for problem gambling (Gainsbury et al, 2014;Hodgins & el-Guebaly, 2000;Rockloff & Schofield, 2004;Tavares et al, 2002).…”
Section: Concluding Commentssupporting
confidence: 66%
See 1 more Smart Citation
“…Deep shame was a near universal emotion amongst participants with self-stigmatizing beliefs, prompting secrecy as the main coping mechanism (Link et al, 2004) to preserve a (problem-free) social and subjective identity (Goffman, 1963). The findings confirmed that perceived and self-stigma are major barriers to seeking help for problem gambling (Gainsbury et al, 2014;Hodgins & el-Guebaly, 2000;Rockloff & Schofield, 2004;Tavares et al, 2002).…”
Section: Concluding Commentssupporting
confidence: 66%
“…This is surprising, given that stigma and shame have been identified as major barriers to help-seeking for problem gambling (Gainsbury, Hing, & Suhonen, 2014;Hodgins & el-Guebaly, 2000;Pulford et al, 2009;Rockloff & Schofield, 2004;Tavares, Martins, Zilberman, & el-Guebaly, 2002). At the time of writing, only five peer-reviewed publications have focused specifically on problem gambling stigma: a review identifying numerous gaps in knowledge and future research directions (Hing, Holdsworth, Tiyce, & Breen, 2014) and four empirical studies, all with samples restricted to university students (Dhillon, Horch, & Hodgins, 2011;Feldman & Crandall, 2007;Horch & Hodgins, 2008.…”
mentioning
confidence: 99%
“…For many problem gamblers, the primary motives for seeking help are the financial problems and concerns (Gainsbury, Hing, & Suhonen, 2014;Hodgins & el-Guebaly, 2000;Pulford et al, 2009). Anderson, Dobbie and Reith (2009) found that during realization and acceptance of problem gambling, the issue of money is important: in their study, a change in behaviour was triggered through mundane, money-related situations together with growing self-awareness of the amounts of money that was spent on gambling.…”
Section: Introductionmentioning
confidence: 99%
“…Ces résultats pourraient avoir des implications tant au niveau de l'intervention auprès des joueurs pathologiques et à risque que de la prévention. Bien que lors des entrevues qualitatives les joueurs ont semblé vouloir être entendus dans leur expérience en abordant ce qu'ils aimaient, la manière dont ils intégraient le poker à leur vie et les stratégies mises en place pour préserver un équilibre, la littérature rapporte que les joueurs à risque ou problématiques sont réticents à venir en traitement (Gainsbury, Hing et Suhonen, 2014). Selon une étude réalisée auprès de plus de 2 000 adultes australiens, bien que 24 % aient révélé être préoccupés par leurs comportements de jeu et pourraient avoir besoin d'aide, seulement 17 % d'entre eux ont eu accès à des services (Davidson et Rodgers, 2010).…”
Section: Discussionunclassified